Efektivitas Komunikasi Relawan Nusantara Rumah Zakat Indonesia Cabang Bengkulu dalam Membangun Altruisme - Detania Natasha; Eceh Trisna Ayuh (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
The purpose of the study was to find out how effective the communication of Indonesian volunteers from the Indonesian zakat house was in building altruism. Qualitative research methods with data collection techniques are participatory observation and interviews. This research is associated with the study of DeVito Theory as an analytical knife in a humanistic approach, there are five general qualities of interpersonal communication, namely 1) openness, 2) empathy, 3) supportiveness, 4) positive attitude. , 5) equality (equality). The results showed that the Nusantara Volunteers of the Indonesian Zakat House Bengkulu Branch built a sense of altruism in society in order to humanize other humans and pay more attention to the people around them. The conclusion of this research is the effectiveness of what is done so that people are interested and moved in building themselves to be more concerned so that a sense of altruism arises in them. Keywords: Altruism, Communication Effectiveness, Home Archipelago Volunteers Indonesian Zakat